Marx and Ho Chi Minh on Educating the Young Generation: Ideological Values for the 21st Century - Thai, Trinh Minh (Kalágatos, 2025)
Marxist philosophy and Ho Chi Minh's thoughts on youth education are pivotal for guiding the holistic development of young generations across historical periods, particularly today. Marx viewed education as a dual-purpose tool for imparting knowledge and fostering human liberation and societal progress. Ho Chi Minh emphasized youth as the "pillars of the nation," advocating for education that nurtures moral, intellectual, physical, and spiritual growth. These values remain vital in the face of rapid technological advancements, globalization, and social complexities. Effective youth education must integrate practical experiences, critical thinking, creativity, and social responsibility. Moreover, embedding humanistic values, patriotism, and self-reliance within the curriculum guided by Ho Chi Minh's ideals enhances its impact. Aligning educational strategies with Marxist and Ho Chi Minh’s principles, we can cultivate well-rounded individuals and global citizens capable of addressing the demands of the modern era.